Genetic conservation of two grouper species (Epinephelus) through DNA barcoding in Palu Bay, Indonesia - Muh. Saleh Nurdin; Nur Hasanah; Novalina Serdiati; Aswad Eka Putra; Kasim Mansyur; Achmad Rizal (Arwana: Jurnal Ilmiah Program Studi Perairan, 2025)
Grouper resources in various Indonesian waters face several issues, primarily due to decreased total catch and overexploitation of stocks. The risk of overfishing can impact genetic diversity. Therefore, understanding the population structure of grouper is crucial as an initial step in identifying potential genetic declines. Information on population structure is obtained through molecular approaches using the Cytochrome Oxidase subunit I as a DNA marker. The research aims to reconstruct the phylogenetics of grouper and analyze their genetic structure in Palu Bay, Central Sulawesi, for genetic conservation purposes. The collected samples consisted of two species from the genus Epinephelus. Fin samples were taken approximately 10 gr and processed for DNA extraction. The extraction method followed the DNeasy Tissue Kits protocol. The extraction results were then analyzed by Polymerase Chain Reaction followed by DNA sequencing using the Sanger dideoxy method. Phylogenetic reconstruction used MEGA X software, while haplotype diversity (Hd), nucleotide diversity (Pi), and fixation index (Fst) analysis used ARLEQUIN 3.1 software. Phylogenetic reconstruction found two different grouper species clades, Epinephelus coioides and E. bontoides. Genetic diversity in E. coioides was found to be moderate, while it was low in E. bontoides. Genetic conservation approaches through hybridization can be applied to both grouper species in Palu Bay as an effort to recover declining genetic resources.